2010
DOI: 10.1007/s10344-010-0479-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing reproductive performance of northern bobwhite in South Florida

Abstract: Reproductive success is a critical component of individual fitness, and also an important determinant of growth rates of populations characterized by early maturity and high fecundity. We used radiotelemetry data collected during 2003-2008 to estimate reproductive parameters in a declining northern bobwhite (Colinus virginianus) population in South Florida, and to test hypotheses regarding factors influencing these parameters. The overall clutch size was 12.10±0.22, but females laid more eggs in their first cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 42 publications
1
18
2
Order By: Relevance
“…Similarly, mean hatching success (85.5 ± 2.9%) was slightly lower than the population average reported by Sandercock et al (85–95%; ), and our estimates of re‐nesting and double‐clutching were exceptionally low; no males and only 13.8% of females ( n = 12) were known to re‐nest after a failed nesting attempt. Our re‐nesting rate was less than half of what was reported in a study from Florida (0.28; Rolland et al ) and below the range reported by Sandercock et al (25­–69%; ).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Similarly, mean hatching success (85.5 ± 2.9%) was slightly lower than the population average reported by Sandercock et al (85–95%; ), and our estimates of re‐nesting and double‐clutching were exceptionally low; no males and only 13.8% of females ( n = 12) were known to re‐nest after a failed nesting attempt. Our re‐nesting rate was less than half of what was reported in a study from Florida (0.28; Rolland et al ) and below the range reported by Sandercock et al (25­–69%; ).…”
Section: Discussioncontrasting
confidence: 74%
“…Our re-nesting rate was less than half of what was reported in a study from Florida (0.28; Rolland et al 2011) and below the range reported by Sandercock et al (25-69%;2008).…”
Section: Modelcontrasting
confidence: 75%
“…In addition to range shifts, there is increasing evidence that climate is linked to avian survival and productivity (Rolland et al. , Skagen and Adams , Cox et al. , b , Jenouvrier ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to range shifts, there is increasing evidence that climate is linked to avian survival and productivity (Rolland et al 2011, Skagen and Adams 2012, Cox et al 2013a, b, Jenouvrier 2013. Dybala et al (2013) found a direct effect of winter temperature on adult survival and an indirect effect of prior rainy season on juvenile survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation